OPERATING AND FINANCIAL EFFICIENCY OF SELECTED TELECOMMUNICATION COMPANIES IN INDIA: A COMPARATIVE STUDY OF RELIANCE JIO, BHARTI AIRTEL, AND VODAFONE IDEA - Dr.S. Kavitha (The Bioscan, 2024)
This study examines the operating and financial efficiency of selected telecommunication companies in India. The analysis focuses on Reliance Jio, Bharti Airtel, and Vodafone Idea. The telecom sector has become a crucial contributor to economic growth, digital connectivity, and technological advancement. The study evaluates operating margin, revenue growth, return on assets, profitability, and debt management. The findings indicate that operational excellence significantly influences financial performance and sustainability.